Early identifiation of specific dyslexia syndrome in children with neurological diseases - Τζούφη, Μερόπη; Ζακοπούλου, Βικτώρια; Βέρμπη, Χάιδω; Νάκου, Ηλιάδα; Μαυρέας, Βενετσιάνος; Σιαμοπούλου-Μαυρίδου, Αντιγόνη (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF